Decentralization on the example of the Yemeni water sector - Mewes, Katharina; SpringerLink (Online service). (Wiesbaden VS Verlag für Sozialwissenschaften, 2011)
Annotation Decentralization is widely discussed in the literature. Katharina Mewes gives an introduction to the theoretical and practical dimensions of decentralization in an accessible and systematic way. On the example of the reform process for the Yemeni Urban Water Supply and Sanitation (UWSS) sector, she links the theoretical, conceptual, and methodological aspects of decentralization to empiric problems. This book is valuable reading for researchers and students of political science, environmental and water studies, development researchers and regional experts
Electronic reproduction.
Keywords: Decentralization in government -- Yemen (Republic).; Municipal water supply -- Yemen (Republic).; Decentralization in government -- Yemen (Republic).; Municipal water supply -- Yemen (Republic).; Electronic books